A probabilistic approach to evaluate salivary microbiome in forensic science when the Defense says: `It is my twin brother'. (March 2022) - Bozza, S.; Scherz, V.; Greub, G.; Taroni, F.
Abstract: Salivary microbiota profiles may represent a valid contribution to forensic investigation when standard DNA genotyping methods fail. Starting from questioned and control materials in the form of saliva, the evidence can be expressed by means of a distance between those materials taking into account specific aspects of the microbiota composition. The value of the evidence for forensic discrimination purposes is quantified by means of a Bayes' factor, that allows one to overcome the major limitations and pitfalls of intuition connected to the use of cut-off values as a mean of decision. Highlights: salivary microbiota composition to support discrimination between related individuals. Beta-diversity indeces to highlight taxonomical differences between pairs of individuals. a probabilistic approach to evaluate salivary microbiome.